The Effect of Technical Performance on Patient Outcomes in Surgery: A Systematic Review. Issue 3 (March 2017) - Fecso, Andras B.; Szasz, Peter; Kerezov, Georgi; Grantcharov, Teodor P.
Abstract : Objective: Systematic review of the effect of intraoperative technical performance on patient outcomes. Background: The operating room is a high-stakes, high-risk environment. As a result, the quality of surgical interventions affecting patient outcomes has been the subject of discussion and research for years. Methods: MEDLINE, EMBASE, PsycINFO, and Cochrane databases were searched. All surgical specialties were eligible for inclusion. Data were reviewed in regards to the methods by which technical performance was measured, what patient outcomes were assessed, and how intraoperative technical performance affected patient outcomes. Quality of evidence was assessed using the Medical Education Research Study Quality Instrument (MERSQI). Results: Of the 12, 758 studies initially identified, 24 articles (7775 total participants) were ultimately included in this review. Seventeen studies assessed the performance of the faculty alone, 2 assessed both the faculty and trainees, 1 assessed trainees alone, and in 4 studies, the level of the operating surgeon was not specified. In 18 studies, a performance assessment tool was used. Patient outcomes were evaluated using intraoperative complications, short-term morbidity, long-term morbidity, short-term mortality, and long-term mortality. The average MERSQI score was 11.67 (range 9.5–14.5). Twenty-one studies demonstrated that superior technical performance was related to improved patient outcomes. Conclusions: The results of this systematic review demonstrated that superior technical performance positively affects patient outcomes. Despite this initial evidence, more robust research is needed to directly assess intraoperative technical performance and its effect on postoperative patient outcomes using meaningful assessment instruments and reliable processes.